Automation of spatial and mutual orientation in assembly operations on the example of M8 screw - Kagankiewicz, Filip (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2019)
The article deals with issues of spatial and mutual orientation on the example of the MB screw. In particular, the focus was on issues related to the automation of such a process. An exemplary pre-assembly line was proposed, in which devices for changing orientation of part were used. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)